THE EFFECT OF THE DURATION OF INHALED NICOTINE EXPOSURE TO THE NUMBER OF LEYDIG, SPERMATOGONIUM, AND SERTOLI CELLS ON THE SPRAGUE-DAWLEY STRAIN WHITE RATS - Hoesain, Fadil Pramudhya; Soebadi, Doddy M.; Djatisoesanto, Wahjoe (Indonesian Journal of Urology, 2020)
Objective: To analyze the differences of the number of Leydig, spermatogonium, and Sertoli cells in mice, after being given nicotine inhalation, and the effect of recovery when nicotine stopped. Materials & Methods: This is experimental studies with a post-test only control group design. The sample used was 36 adult male mice (10-12 weeks) (Rattus Norvegicus) Sprague-Dawley strain, which were divided into three groups. P1 group was given nicotine inhalation at a dose of 4 mg/kg/day for 15 days, P2 group was given nicotine inhalation at a dose of 4 mg/kg/day for 15 days and was free of treatment for 15 days. The control group (NC) has no treatment at all. Histological examination and calculation of Sertoli cells, Leydig cell, and spermatogonium were processed within 1 hour after terticular sample collection. Then carried out to statistical analysis. 100x and 400x magnification is used to obtain the histopathological. Results: Post-hoc LSD test for each variable (Leydig cells, Sertoli cells, and spermatogonium), showed that the NC group had a significantly higher number compared to group P1. P2 group has a significantly higher number compared to group P1. There is no significant difference between the NC group and the P2 group. There was a structural difference in the sample testicles which exposed to nicotine. Conclusion: Nicotine exposure with a dose of 4 mg/kg/day for 15 days has a significant effect on decreasing the number of Leydig cells, spermatogonium cells, and Sertoli cells in rats and giving a free-treatment period for 15 days, giving the testis time to do recovery and regeneration (the reversible damage of testicular structure).